Structural modification of indium implanted glassy carbon by thermal annealing and SHI irradiation. (October 2017) - Njoroge, E.G.; Sebitla, L.D.; Theron, C.C.; Mlambo, M.; Hlatshwayo, T.T.; Odutemowo, O.S.; Skuratov, V.A.; Wendler, E.; Malherbe, J.B.
Abstract: The structural changes, migration behaviour of indium (In) implanted into glassy carbon (GC) and the effect of annealing on radiation damage introduced by ion implantation have been investigated. The GC substrates were implanted with 360 keV indium ions to a fluence of 2.0 × 10 16 ions/cm 2 at room temperature (RT) and 350 °C. The RT implanted samples were isochronally annealed in vacuum between 200 and 1000 °C for 1 h. The 350 °C implanted GC substrates were irradiated 167 MeV with Xe 26+ ions at room temperature to a maximum fluence of 5.0 × 10 14 ions/cm 2 . The implanted GC structure was damaged and had an almost amorphized structure. Annealing of the RT implanted samples resulted in some recrystallization which increased with temperature and the diffusion behaviour of implanted In. Fickian diffusion of implanted In started after annealing at 300 °C, however, structural changes in the GC were observed after annealing at 200 °C. Annealing at 400 and 600 °C resulted in the diffusion of In toward the surface of GC accompanied by a loss of In. The SHI irradiation of the 350 °C implanted samples at increasing fluence, did not result in a detectable migration of implanted In. Highlights: GC surface regions were transformed to highly disordered structure by indium ions implantation. The RT implanted In profiles are stable after annealing up to 300 °C. Fickian diffusion was observed at 300 °C. At 400–600 °C In diffusion toward the surface and out of the GC substrate. No In diffusion due to SHI irradiation but only led to further damaging of the implanted region.